Direct comparison of oligochaete erythrocruorins as potential blood substitutes. Issue 2 (19th July 2017) - Zimmerman, Devon; DiIusto, Matthew; Dienes, Jack; Abdulmalik, Osheiza; Elmer, Jacob J.
Abstract: While many blood substitutes are based on mammalian hemoglobins (e.g., human hemoglobin, HbA), the naturally extracellular hemoglobins of invertebrates (a.k.a. erythrocruorins, Ecs) are intriguing alternative oxygen carriers. Specifically, the erythrocruorin of Lumbricus terrestris has been shown to effectively deliver oxygen in mice and rats without the negative side effects observed with HbA. In this study, the properties of six oligochaete Ecs ( Lumbricus terrestris, Eisenia hortensis, Eisenia fetida, Eisenia veneta, Eudrilus eugeniae, and Amynthas gracilis ) were compared in vitro to identify the most promising blood substitute candidate(s). Several metrics were used to compare the Ecs, including their oxidation rates, dissociation at physiological pH, thermal stability, and oxygen transport characteristics. Overall, the Ecs of Lumbricus terrestris (LtEc) and Eisenia fetida (EfEc) were identified as promising candidates, since they demonstrated high thermal and oligomeric stability, while also exhibiting relatively low oxidation rates. Interestingly, the O2 affinity of LtEc ( P 50  = 26.25 mmHg at 37° C) was also observed to be uniquely lower than EfEc and all of the other Ecs ( P 50  = 9.29–13.62 mmHg). Subsequent alignment of the primary sequences of LtEc and EfEc revealed several significant amino acid substitutions within the D subunit interfaces that may be responsible for this significant change in O2 affinity. Nonetheless, these results show that LtEc and EfEc are promising potential blood substitutes that are resistant to oxidation and denaturation, but additional experiments will need to be conducted to determine their safety, efficacy, and the effects of their disparate oxygen affinities in vivo.